A process calculus for energy‐aware multicast communications of mobile ad hoc networks. Issue 3 (24th February 2012) - Gallina, Lucia; Rossi, Sabina; Gerla, Mario; Maggiorini, Dario; Palazzi, Claudio E.
ABSTRACT Energy conservation is a critical issue in mobile ad hoc networks (MANETs) for both nodes and network lifetime, as only batteries power nodes. In this paper, we present the E‐BUM calculus, an Energy‐aware calculus for Broadcast, Unicast and Multicast communications of MANETs. In order to reason about cost‐effective ad hoc routing protocols, our calculus captures the possibility for a node to control the transmission radius of its communications. We show how to use the E‐BUM calculus in order to prove some useful connectivity properties of MANETs, to control network topology and to reason about the problem of reducing interference. In particular, we formalize the notions of sender‐centred and receiver‐centred interference and provide efficient proof techniques for verifying the absence of interference between a specific set of nodes. Copyright © 2012 John Wiley & Sons, Ltd.